2019
DOI: 10.1177/0308518x19842583
|View full text |Cite
|
Sign up to set email alerts
|

The subjective well-being of homeworkers across life domains

Abstract: This paper extends the view of homeworking as a type of flexible working by employees in organisations aimed at improving work-life balance and job satisfaction, to a type of work that encapsulates significant changes of work towards increased self-employment and casual work, high proportions of which are performed in people's homes. Such changes to work represent a reconfiguration of the spatial separation and relationship between place of work and place of residence. Through homeworking, this paper studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 92 publications
1
60
0
1
Order By: Relevance
“…The privileged socio-economic profile of homeworkers before the COVID-19 crisis is associated with living in well-off neighbourhoods, in particular inner-city neighbourhoods with high proportions of professional workers as well as suburban areas with large properties and high proportions of homeowners (Moos and Skarbursis, 2007). While privileged residential living will have facilitated high job satisfaction reported in previous studies (Reuschke, 2019), many of the 'new' homeworkers in this current crisis are likely to work in an environment that is less suitable for homeworking. This is likely to be true for those in small accommodation, especially in expensive metropolitan housing markets, and those in family households without a spare room that could be used as office space.…”
Section: Inequalities In the Working-at-home Experiencementioning
confidence: 89%
“…The privileged socio-economic profile of homeworkers before the COVID-19 crisis is associated with living in well-off neighbourhoods, in particular inner-city neighbourhoods with high proportions of professional workers as well as suburban areas with large properties and high proportions of homeowners (Moos and Skarbursis, 2007). While privileged residential living will have facilitated high job satisfaction reported in previous studies (Reuschke, 2019), many of the 'new' homeworkers in this current crisis are likely to work in an environment that is less suitable for homeworking. This is likely to be true for those in small accommodation, especially in expensive metropolitan housing markets, and those in family households without a spare room that could be used as office space.…”
Section: Inequalities In the Working-at-home Experiencementioning
confidence: 89%
“…Remote work was found to be related to greater job satisfaction (Binder 2016; Wheatley 2017; Reuschke 2019). However, Wheatley (2017) and Reuschke (2019) find such a positive association between remote work and job satisfaction for employees only and Binder (2016) found a large effect for remote work on job satisfaction only among men but not for women. In contrast, Song and Gao (2019) find that remote work is associated with less happiness and more stress.…”
Section: Remote Work and Satisfaction With Work And Familymentioning
confidence: 98%
“…Concerning the actual outcomes of telework, an extensive literature presents contradictory evidence and conclusions [5]. Several studies find telework to be "successful" insofar as it correlates with desired, positive effects in the lives of teleworkers, particularly as regards perceived job satisfaction and effectiveness, but also as a facilitator of the effective arrangement of work/nonwork commitments and work-life balance [33,38,39,50,51]. On the other hand, research has also repeatedly found that some people working from home encounter new problems [5] and unintended consequences that counterbalance or even outweigh the expected gains (e.g., ineffective work due to household distractions, private life intrusions, workaholism, and professional and personal isolation) [43,52,53].…”
Section: Potential Gains and Drawbacks In Extended Telework As Regardmentioning
confidence: 99%